Learning from errors: A model of individual processes - Maria Tulis; Gabriele Steuer; Markus Dresel (EARLI, 2016)
Errors bear the potential to improve knowledge acquisition, provided that learners are able to deal with them in an adaptive and reflexive manner. However, learners experience a host of different-often impeding or maladaptive-emotional and motivational states in the face of academic errors. Research has made few attempts to develop a theory that focuses on learning from errors (with the exceptions of the theory of impasse-driven learning and the theory of negative knowledge) and, in particular, a theoretical framework that focuses on antecedent motivational processes. By integrating theories of self-regulated learning, volition, attributions, and appraisals, we propose a model that highlights individual processes that are characteristic of this specific learning phenomenon. More precisely, our theoretical framework aims to explain how emotional, motivational and self-regulatory processes-influenced by personal and contextual conditions-interact in order to facilitate or impede adaptive dealing with errors and appropriate metacognitions and cognitive activities. Our objective is to provide a framework that allows for the systematic integration of various aspects that have been targeted in previous research and to guide and stimulate future research on learning from errors. As a first evidence for validation, we summarise research findings that address specific parts of the proposed model.